RANCANG BANGUN LEMARI PENGERING BIJI KAKAO BERBASIS MIKROKONTROLER ARDUINO UNO 328P - Minsar Nasution; Edidas Edidas; Almasri Almasri (Universitas Negeri Padang, 2019)
ABSTRACTThe purpose of this research is to design and make a real tool in the form of a drying cabinet for cocoa beans. Because this solution can relieve the farmers who previously drained the cocoa beans in the sun. This drying cabinet uses the Arduiono Uno 328P control and heater element as a heater. This cabinet is also equipped with a DC motor mechanical device to drive the cocoa drying container. This tool is also equipped with a DHT12 sensor which is a resistive sensor whose value changes depending on the water content of the cocoa beans. The sensor plays a role in detecting the temperature and humidity of the seeds in the cacao drying room. Then the output inverting amplifier voltage is read by the ADC Arduino UNO 328p microcontroller, which is then processed and displayed on the LCD. The test results showed that the measuring instrument made was able to measure the amount of water contained in cocoa beans in the range of water content measurement from 60% to 7.5%. Keyword: Cocoa Beans, Temperature, Arduino, DC Motor, DHT Sensor